Modern physics in the museum: Shaping a UK national collection in the twentieth century. (17th October 2018) - Boyle, Alison
Abstract: This paper examines how modern physics was collected and displayed in the UK over the (long) twentieth century, focusing on the national collections in the Science Museum, London. The emergence and establishment of modern physics roughly overlaps with the development of distinct science and technology museums. This provides an opportunity to explore how collections are shaped in response to scientists' own narratives of their professional identities, institutional or political priorities, and how certain aspects of the material culture of a scientific area can become closely intertwined with its public image. By tracing the movement of a well-known artefact of modern physics – a cathode-ray tube used by J. J. Thomson in his 'electron' experiments – I show how collection boundaries could be porous, although overall collection framings persisted.